313 Sacroiliac Joint Fusion Using Robotic Navigation: Technical Note and Case Series. (1st April 2022) - Wang, Timothy Y.; Bergin, Stephen M.; Murphy, Kelly R.; Mehta, Vikram; Sankey, Eric W.; Abd-El-Barr, Muhammad M.; Grossi, Peter M.; Than, Khoi Duc
Abstract : INTRODUCTION: Degenerative sacroiliac (SI) joint disease can cause significant pain and disability. Patients undergoing SI fusion can oftentimes experience significant improvements in pain and quality of life. METHODS: Patients undergoing standalone SI joint fusion from July 2020 through June 2021 were retrospectively enrolled. Demographic and comorbid variables collected included age, sex, body mass index, and laterality. Recorded operative variables included operative time, estimated blood loss, and any intraoperative complications. Pain scores in the post-anesthesia care unit (PACU) were recorded using the visual analogue scale (VAS) every 30 minutes, as were total morphine equivalents for PACU administered intravenous and oral narcotic pain medications according to pain scales. Length of stay and any postoperative complications including 30-day inpatient admissions or emergency department (ED) presentations were also recorded. Intraoperative radiation exposure was also recorded. RESULTS: A total of 8 patients were analyzed. Average patient age was 65.6 ± 7.6 years with BMI of 28.2 ± 3.6 kg/m 2 . Four (50.0%) patients were female and equal numbers of left and right-sided SI joint fusions were performed. Average operative time was 56 ± 9 minutes, and average estimated blood loss was 22.5 ± 18.7cc. Average intraoperative radiation exposure was 12.7 ± 6.7 mGy and there were no intraoperative complications. Average pain scores in PACU were 5.1 ± 1.0 with average maximum pain score of 7.6 ± 1.7 and average minimum pain score of 2.0 ± 2.2. Average narcotic administration in PACU was 22.8 ± 11.1 morphine equivalents. Average length of stay was 0.4 ± 0.8 days, with 75% of patients discharged on the same day of surgery. Two patients required inpatient stay: one patient required intravenous pain medications overnight and one patient had shortness of breath without clear etiology, resolved without sequela. No patients presented back to the ED or were admitted within 30-days of surgery. CONCLUSION: Robot-navigated SI joint fusion is a feasible and reproducible method for addressing refractory sacroiliac joint disease. Further investigation on clinical outcomes and long-term fusion rates is needed, as are studies comparing robot-navigated SI joint fusion to more traditional techniques.